Representasi Pengkhianatan pada Film The Last Supper (2025) (Analisis semiotika jhon fiske) - Fellix Joe Chandra; Muhammad Irfan; Faikoh Umairoh (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research aims to examine how betrayal is represented in the film The Last Supper (2025). The study employs a qualitative approach using John Fiske’s semiotic theory, which focuses on three levels of codes: reality, representation, and ideology. Data were collected through visual observation of the film’s scenes and analyzed to identify signs and underlying meanings within the actions of the characters. The findings reveal a total of nine betrayal scenes, segmented into 52 image shots that were analyzed in depth. These scenes primarily depict the betrayals committed by Judas Iscariot and Peter against Jesus Christ. The analysis shows that betrayal is not merely presented as a dramatic motif but is constructed as an ideological representation that reflects power relations, social pressure, and human moral dilemmas. The film serves as a cultural text that constructs meaning through visual symbols, gestures, expressions, and dialogue. As such, it can be interpreted as a form of social criticism against systems of power that influence individual behavior. Therefore, the film functions not only as entertainment but also as a discursive space that voices fundamental human issues.